Investigation into hardness changes of Pd 11.1 at.% Cu and Pd 11.1 at .% Nb after heat treatments - Finkelstein, Luke Marcus (Centre for Materials Engineering, 2015)
Two alloys, Pd 11.1 at.% Cu and Pd 11.1 at.% Nb, predicted to form the A8B ordered structure, were investigated. Prior deformation with systematic heat treatments was used to promote ordering, hardness tests were used to detect changes in the microstructure, which might result from ordering. The Pd-Cu alloy and Pd-Nb alloy did not exhibit any significant hardness changes when heat treated. Transmission Electron Microscopy (TEM) was used to aid detection of any A8B ordered phase in the Pd-Cu alloy. It was concluded that no ordering had occurred and any initial hardness variation was anomalous. The Pd-Nb alloy was further characterised using Differential Scanning Calorimetry, but no transformation was observed. The Pd-Cu alloy was predicted by other workers (after commencement of this project) to have a very low ordering temperature, which probably accounts for the lack of ordering at the temperatures reported here. The Pd-Nb alloy is concluded to be extremely slow in atomic rearrangement, so that unfavourable thermodynamics prevented ordering of the alloy during this project.